Metionina e colina em dietas para juvenis de tilápia do Nilo, desempenho produtivo, morfologia hepática e muscular - Graciano, Thêmis Sakaguti (2009)
This study was conducted to evaluate the effects of methionine and / or choline on performance, morphology of liver and white muscle of Nile tilapia, Supreme strain. Onehundred and sixty fish with average weight of 77 ± 0.8 g were distributed in 16 tanks (1000 L each) with 10 fish/tank, in a recirculation system, during 87 days. Four diets with 33% CP and 3,000 kcal DE kg-1 were used: control (CT), supplemented with 0.3% methionine (MT), 0.2% of choline (LC) or 0.3% of 0.2% of methionine and choline (MT + CL). Fish were fed were hand fed until apparent satiation. Livers were macroscopically and microscopically examined and characterized by staining of hepatic parenchyma with Hematoxilin-Eosin, and for inclusion glycogenic histochemistry (P.A.S.) and lipid (Sudan III). Samples of white muscle of dorsal region were used for morphological and morphometric evaluation of the minor diameter of the cell. No effects of methionine and/or choline on daily weight gain, feed conversion, fillet yield, hepatosomatic index, visceral fat and white muscle fiber diameter were observed. Fish fed diets supplemented with choline and methionine showed lower fat content in the fillets. Fish fed CL and CL+MT showed higher glycogenic inclusion and lower lipidic inclusion in the liver, compared to fish fed CT and MT diets. It was concluded that choline supplementation reduces lipid inclusion in the liver and fatty degeneration occurs in fish fed CT and MT diets.